Pelaksanaan Pengelolaan Dan Pemeliharaan Barang Bukti Dalam Proses Penyidikan Tindak Pidana Di Polres Grobogan - Kiswadi, Kiswadi; Erief, Eva; Anwar, Khoirul (PMIH Untag Semarang, 2024)
The research entitled ‘‘Implementation of Management and Maintenance of Evidence in the Process of Investigating Crimes at the Grobogan Police Station‘‘, has a problem formulation regarding the mechanisms and obstacles in implementing the management and maintenance of evidence at the Grobogan Police Station.criminal investigation process at Grobogan Police. This research aims to determine the implementation mechanism for managing and maintaining evidence in the process of investigating criminal acts at the Grobogan Police and to determine the obstacles in managing and maintaining evidence in the process of investigating criminal acts at the Grobogan Police. Based on the data analysis carried out, it can be concluded that the evidence received by the prisoner care unit and evidence from investigators was obtained from the confiscation or search process through the minutes of handing over of evidence by investigators, after which the prisoner care and evidence unit checked the evidence with a report.